PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN - NURJANAH NURJANAH; Jurica Lucyanda (JRAK: Journal of Accounting Research and Computerized Accounting, 2013)
The objective of this study was to analyze the influence of corporate charaterictics (size, profitability,leverage and age of firm) on corporate social responsibility disclosure. This research is an empiricalstudy using logistic regression analysis. The sample used in this study was the secondary data fromIndonesian Stock Exchange, for year 2007-2008. The sample was taken using purposive sampling methodand those which meeting the selection criteria. The sample used was 36 annual reports. Hypothesis testingby logistic regression analysis showed that all corporate characteristics such as size, profitability,leverage and age of firm had no significant influence on corporate social responsibility disclosure.